Peningkatan Produktivitas Udang Vaname Di Kolam Bundar Dengan Sistem Bioflok (Telaah Pustaka) - Gitri Maudy; Junianto Junianto (Universitas Mataram, 2024)
Vannamei shrimp is one of the commodities with high economic value. The increasing market demand for vannamei shrimp presents a significant opportunity for Indonesia. The high demand for vannamei shrimp aquaculture production necessitates the implementation of efficient and environmentally friendly farming technologies. One such technology is the Biofloc system. The application of the biofloc system in round ponds can enhance the growth and survival rates of vannamei shrimp. This method employs a literature review approach, analyzing both national and international journals accessed through online platforms like Google Scholar. The literature review was conducted in September 2024. The benefits of applying biofloc technology in vannamei shrimp farming in round ponds include increased productivity and growth of the shrimp.